PERBANDINGAN PERILAKU PENGGUNAAN KONDOM DAN PELICIN SECARA KONSISTEN PADA WARIA BINAAN PONPES DAN NON PONPES DI YOGYAKARTA Comparison Behavior Of Use Condoms And Lubricant Consistently In Tranvestite In PonpesWaria Al Fatah And Non Ponpes In Yogyakarta - Aliyatur Rosyidah (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Based on American of The Foundation for AIDS Research (amfAR) found that transvestites19 times more infected with HIV than the general society. Nearly 50% transvestites who become members of the target PonpesWaria Al Fatah sentenced to suffer from HIV. Integrated Biological and Behavioral Survey (STBP) of 2011 states that the inconsistent condom use on transvestites is still low at less than 50%.Whereasin 2014 KPAN reportedthat the distributionof male condomsbyoutletreaches338 783. Objective of this study to compare the behavior of condoms and lubricants consistently on PonpesWaria Al Fatah and Non Ponpes in Yogyakarta. The method used is descriptive comparative and cross sectional approach. The first population is transvestites built PonpesWaria Al Fatah by the number 23 and the samples taken are all using sampling methods saturated and second population is transvestites Non Ponpes consisting of 8 transvestites community with the number 121 transvestites using Proportionate Stratified Random Sampling with the amount of sample 23 people. Analyzed using univariate and bivariate statistical t test and Mann Whitney as an alternative test (significance level 0.05). These results indicate that transvestites Non Ponpes more consistent in the use of condoms and lubricant compared with the PonpesWaria Al Fatah. Age transvestites target PonpesWaria Al Fatah largely ≥ 44 years (78.3%), while transvestites Non Ponpes<44 years (69.6%), the last education most widely adopted PonpesWaria Al Fatah is Senior High School (43.5%) while Non Ponpes are Junior High School (43.5%) and all respondents have never been married. Results of statistical tests show that there are differences in perception variable barrier (0.039), religiosity (0,000), the frequency of anal sex (0,030), the frequency of anal sex using condoms (0.027) and the frequency of unprotected anal sex (0,020). It is expectedthatdisseminate tothetransvestitescouplestousecondoms and lubricantsconsistently.